Niobium-containing thick-gauge weathering steel and rolling method thereof

By optimizing the chemical composition and preparation process of weathering steel, especially adding rare earth element RE and adjusting alloy element ratio, and using processes such as electroslag remelting, cooling, aging treatment and shot peening strengthening, combined with an intelligent production system, the problems of insufficient comprehensive performance and low production efficiency of existing weathering steels have been solved, and the high strength, oxidation resistance and corrosion resistance have been significantly improved.

CN119843184AActive Publication Date: 2025-04-18ANHUI KUAYU STEEL STRUCTURE GRID ENG CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411825117.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing weathering steels have shortcomings in their comprehensive properties such as high strength, oxidation resistance and corrosion resistance, and the traditional preparation process control accuracy is not high, resulting in low production efficiency and unstable product quality.

Method used

By optimizing the chemical composition design, especially adding rare earth elements RE and adjusting the ratio of elements such as Nb, V, Zr, etc., the matrix strength and microstructure structure of the steel are significantly improved. At the same time, the electroslag remelting process, three-stage cooling, aging treatment and dual-die shot peening strengthening are adopted, combined with an intelligent production system, and the parameters of each production link are accurately controlled to improve production efficiency and product quality.

Benefits of technology

It has achieved significant improvements in steel in terms of yield strength, tensile strength, elongation and corrosion resistance, ensuring the application performance of high-strength oxidation-resistant weathering steel, and improving the production efficiency and product quality stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of metal material science and engineering, in particular to niobium-containing thick-gauge weathering resistant steel and a rolling method thereof.The niobium-containing thick-gauge weathering resistant steel comprises, by weight, 0.06%-0.10% of C, 0.15%-0.35% of Si, 0.80%-1.20% of Mn, not larger than 0.015% of P, not larger than 0.005% of S, 0.025%-0.045% of Nb, 0.05%-0.10% of V, the balance Fe and inevitable impurities. The high-strength anti-oxidation weathering steel comprises the following components in percentage by weight: 0.02%-0.05% of Zr, 0.40%-0.60% of Cu, 0.60%-1.00% of Cr, 0.30%-0.50% of Ni, 0.10%-0.30% of Mo and the balance of Fe and inevitable impurities. According to the high-strength anti-oxidation weathering steel disclosed by the invention, the content of each alloy element is controlled through chemical component design, and particularly, the rare earth element RE is added and the ratio of Nb, V, Zr and other elements is optimized, so that the high-strength anti-oxidation weathering steel has the advantages that the high-strength anti-oxidation weathering steel can be obtained; and the matrix strength of the steel is remarkably improved, and meanwhile optimization of the microstructure is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material science and engineering technology, and in particular to a niobium-containing thick-gauge weathering steel and a rolling method thereof. Background Art

[0002] In the existing technology, although weathering steel has certain corrosion resistance and strength, it still has deficiencies in comprehensive performance in terms of high strength, oxidation resistance and corrosion resistance. The chemical composition design of traditional weathering steel is often conservative, and the ratio and content control of alloy elements are not precise enough, which makes it difficult for the strength and corrosion resistance of steel to reach a high level at the same time. In addition, the traditional preparation process is relatively backward, and the control accuracy of steps such as heating, hot rolling, cooling and aging treatment is not enough, which affects the microstructure and performance stability of the steel. Especially in terms of production efficiency, the traditional production method lacks intelligent and automated control, resulting in low production efficiency and difficulty in ensuring product quality.

[0003] At present, the market demand for high-strength and excellent anti-oxidation weathering steel is increasing, and the weathering steel in the prior art is obviously insufficient in meeting these demands. Therefore, there is an urgent need for an innovative weathering steel and its preparation method to solve the problems of insufficient comprehensive performance and low production efficiency of the weathering steel in the prior art. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a niobium-containing thick-gauge weathering steel and a rolling method thereof. The high-strength anti-oxidation weathering steel of the present invention controls the content of each alloy element through chemical composition design, especially adds rare earth element RE and optimizes the ratio of elements such as Nb, V, and Zr, which significantly improves the matrix strength of the steel and promotes the optimization of the microstructure, including the reasonable distribution and size control of ferrite grain size, pearlite lamellar spacing, and carbonitride and oxide particles. The fine control of these microstructures enables the steel to exhibit excellent comprehensive performance in terms of yield strength, tensile strength, elongation, and corrosion resistance, providing a broader space for the application of high-strength anti-oxidation weathering steel.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] In a first aspect, a high-strength anti-oxidation weathering steel is provided, wherein the chemical composition of the weathering steel is calculated by weight percentage, and the C content is 0.06%-0.10%, the Si content is 0.15%-0.35%, the Mn content is 0.80%-1.20%, the P content does not exceed 0.015%, the S content does not exceed 0.005%, the Nb content is 0.025%-0.045%, the V content is 0.05%-0.10%, the Zr content is 0.02%-0.05%, the Cu content is 0.40%-0.60%, the Cr content is 0.60%-1.00%, the Ni content is 0.30%-0.50%, the Mo content is 0.10%-0.30%, and the rest is Fe and unavoidable impurities;

[0009] The thickness of the weathering steel is between 20mm and 35mm.

[0010] Furthermore, the weathering steel contains 0.003%-0.008% by weight of rare earth element RE, and lanthanum La and cerium Ce in the rare earth elements are present in a mass ratio of 2:1-3:1.

[0011] Furthermore, the yield strength of the weathering steel is not less than 500MPa, the tensile strength is not less than 650MPa, the elongation is not less than 28%, the corrosion rate in the neutral salt spray test is not more than 0.008mm / a, and the oxidation weight gain rate in the 800℃ high temperature oxidation test is not more than 0.1mg / cm 2 ·h.

[0012] Furthermore, the microstructure of the weathering steel is ferrite + pearlite + dispersed carbonitride particles + a small amount of nanometer-sized oxide particles, wherein the ferrite grain size is 3μm-8μm, the pearlite interlamellar spacing is 0.1μm-0.3μm, the average size of the carbonitride particles is 10nm-50nm, and the oxide particles are mainly Cr2O3 and ZrO2, with an average size of 5nm-20nm.

[0013] In a second aspect, a high-strength anti-oxidation weathering steel rolling method is provided, wherein the specific steps of the rolling method are:

[0014] a. The chemical composition of claim 1 is prepared by electroslag remelting to smelt molten steel, and then cast into ingots after refining;

[0015] b. Heating the steel ingot, heating temperature 1180℃-1280℃, keeping warm for 2.5-3.5 hours, using segmented variable power during heating, the first stage power is 60%-70% of the maximum power, the second stage power is 80%-90% of the maximum power;

[0016] c. After hot rolling, the steel ingot is heated, the starting temperature of rough rolling is 1080℃-1180℃, the final rolling temperature of rough rolling is 980℃-1080℃, the starting temperature of finishing rolling is 920℃-1000℃, the final rolling temperature of finishing rolling is 830℃-870℃, and the deformation amount of each pass during finishing rolling is 10%-15%;

[0017] d. The hot-rolled steel is cooled in three stages. The first stage is cooled at a rate of 20°C / s-30°C / s to 600°C-700°C. The second stage is cooled at a rate of 10°C / s-20°C / s to 400°C-500°C. The third stage is cooled at a rate of 5°C / s-15°C / s to room temperature.

[0018] e. After cooling, the steel is subjected to aging treatment at a temperature of 550°C-650°C for 3-5 hours. After aging treatment, shot peening is performed with a shot peening intensity of 0.3mm-0.5mm.

[0019] Furthermore, in the step b, the atmosphere in the furnace when the steel ingot is heated is a mixed atmosphere of argon and hydrogen, and the volume ratio of hydrogen content is 3%-8%.

[0020] Furthermore, in the step c, an online induction heating device is arranged between the rough rolling and the finish rolling to raise the temperature of the steel to 950°C-1050°C and maintain it for 1-2 minutes.

[0021] Furthermore, in the step e, the shot peening strengthening after aging treatment adopts dual-medium shot peening as follows: glass beads are first used for pre-shot peening, the glass beads have a particle size of 0.2mm-0.3mm, and the shot peening pressure is 0.2MPa-0.3MPa. After the pre-shot peening, steel shots are used for main shot peening, the steel shots have a particle size of 0.4mm-0.6mm, and the shot peening pressure is 0.4MPa-0.6MPa.

[0022] Furthermore, the rolling method includes an intelligent production system, wherein the system includes a raw material batching unit, an electroslag remelting unit, an ingot heating unit, a hot rolling unit, a three-stage cooling unit, an aging treatment unit, a dual-medium shot peening unit, and a central control unit;

[0023] The raw material batching unit performs accurate batching according to the chemical composition described in claim 1;

[0024] The electroslag remelting unit performs the electroslag remelting process to refine the molten steel and cast the steel ingots;

[0025] The ingot heating unit has the functions of accurately controlling the heating temperature at 1180℃-1280℃, holding time of 2.5-3.5 hours, segmented variable power: the first stage power is 60%-70% of the maximum power, the second stage power is 80%-90% of the maximum power, and the furnace atmosphere, in which argon and hydrogen are mixed, with a hydrogen content of 3%-8% by volume, and transmitting data to the central control unit;

[0026] The hot rolling unit can be operated at a starting temperature of 1080℃-1180℃ for rough rolling and a final rolling temperature of 980℃ for rough rolling.

[0027] -1080℃, finishing rolling start temperature 920℃-1000℃, finishing rolling final rolling temperature 830℃-870℃ and finishing rolling deformation of 10%-15% for each pass, and the steel temperature is raised to 950℃-1050℃ and maintained for 1-2 minutes by an online induction heating device between rough rolling and finishing rolling, while the rolling force and rolling temperature are monitored in real time and fed back to the central control unit;

[0028] The three-stage cooling unit cools the steel at a first stage cooling rate of 20°C according to the instructions of the central control unit.

[0029] / s-30℃ / s cooling to 600℃-700℃, the second cooling rate is 10℃ / s-20℃ / s cooling to 400℃-500℃, the third cooling rate is 5℃ / s-15℃ / s cooling to room temperature;

[0030] The aging treatment unit accurately controls the aging temperature at 550℃-650℃ and the aging time at 3-5 hours. The dual-media shot peening unit can perform pre-shot peening with glass beads of 0.2mm-0.3mm in diameter and shot peening pressure of 0.2MPa-0.3MPa as required, and then perform main shot peening with steel shots of 0.4mm-0.6mm in diameter and shot peening pressure of 0.4MPa-0.6MPa.

[0031] The central control unit conducts real-time monitoring, data collection and analysis of the entire production process, coordinates the work of each unit based on the feedback data from each unit, and realizes intelligent production control.

[0032] Beneficial Effects

[0033] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0034] 1. The present invention controls the content of each alloying element, especially adds rare earth element RE and optimizes the ratio of alloying elements such as Nb, V, Zr, etc. This chemical composition design not only improves the matrix strength of the steel, but also optimizes the microstructure through the synergistic effect of the alloying elements, such as the ferrite grain size, pearlite interlamellar spacing, and the distribution and size of carbonitride and oxide particles. The optimization of these microstructures significantly improves the yield strength, tensile strength and elongation of the steel, while maintaining good corrosion resistance and oxidation resistance.

[0035] 2. In the preparation process, the present invention adopts the electroslag remelting process to refine the molten steel, three-stage cooling to control the cooling rate of the steel, aging treatment and dual-medium shot peening strengthening, and introduces an intelligent production system. By accurately controlling the parameters of each production link, such as heating temperature, holding time, rolling temperature and deformation, etc., the intelligent monitoring and data acquisition and analysis of the production process are realized. This preparation process and intelligent production system not only improves the production efficiency, but also ensures the stability and consistency of product quality. Through real-time monitoring and feedback adjustment, deviations in the production process can be discovered and corrected in time, thereby producing high-performance, high-quality, high-strength, antioxidant and weathering steel.

[0036] 3. The present invention uses ferrite + pearlite + dispersed carbonitride particles + a small amount of nano-scale oxide particles. This microstructure enables the steel to have excellent corrosion resistance and oxidation resistance while maintaining high strength and good plasticity. The morphology and characteristics of the microstructure can be further optimized by adjusting the alloy element content and preparation process parameters. The adjustment of these microstructures not only improves the mechanical properties of the steel, but also enhances its corrosion resistance and oxidation resistance, thereby broadening the application range of high-strength antioxidant weathering steel. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] Embodiment 1:

[0040] (I) Chemical composition design:

[0041] A high-strength, oxidation-resistant and weathering steel is designed, whose chemical composition, by weight percentage, is as follows: C content is 0.06%, Si content is 0.15%, Mn content is 0.80%, P content is 0.012% (not more than 0.015%), S content is 0.003% (not more than 0.005%), Nb content is 0.025%, V content is 0.05%, Zr content is 0.02%, Cu content is 0.40%, Cr content is 0.60%, Ni content is 0.30%, Mo content is 0.10%, and the rest is Fe and unavoidable impurities. The thickness of the weathering steel is 20 mm.

[0042] (II) Preparation method:

[0043] 1. Electroslag remelting and casting ingots:

[0044] Raw material preparation: accurately weigh the raw materials of each element to ensure that the content of each element meets the design requirements. For example, for carbon, select raw materials such as pig iron or scrap steel with appropriate carbon content. For alloy elements such as niobium (Nb), vanadium (V), zirconium (Zr), etc., use corresponding ferroalloys for addition;

[0045] Electroslag remelting operation: Add the prepared raw materials into the electroslag furnace, and accurately control various parameters during the refining process. During the electroslag remelting process, the selection of slag system is crucial. Use a suitable slag system to ensure the refining effect of the molten steel, remove impurity elements, and control the shape and distribution of inclusions. After refining, pour it into ingots. During the pouring process, strictly control the pouring speed and temperature to ensure that the quality of the ingot is uniform and defect-free.

[0046] 2. Ingot heating:

[0047] Heating equipment selection: Choose a heating furnace with precise temperature control function, which can meet the heating temperature requirement of 1180℃ and can achieve heat preservation for 3.5 hours;

[0048] Segmented variable power control: The first stage of power is 60% of the maximum power. This stage is mainly to slowly preheat the steel ingot, so that the internal temperature of the steel ingot rises evenly and reduces the generation of thermal stress. The second stage of power is 80% of the maximum power. After the steel ingot is preheated to a certain degree, the heating power is increased to accelerate the steel ingot to reach the target heating temperature;

[0049] Atmosphere control in the furnace: The atmosphere in the furnace is a mixed atmosphere of argon and hydrogen, with a hydrogen content of 3% by volume. Argon is used as a protective gas to prevent the steel ingot from oxidizing during heating, while hydrogen has a certain reducing effect, which helps to further remove a small amount of oxide impurities on the surface of the steel ingot and improve the purity of the steel. Before the mixed gas is introduced, the furnace is first vacuumed to remove the air in the furnace, and then argon and hydrogen are introduced according to the set gas flow and ratio. The gas flow is accurately controlled by a gas flow controller to ensure a stable atmosphere.

[0050] 3. Hot rolling:

[0051] Rolling equipment preparation: Select appropriate roughing mill and finishing mill to ensure that the process requirements of roughing start temperature of 1080℃, roughing final rolling temperature of 980℃, finishing start temperature of 920℃, and finishing final rolling temperature of 830℃ can be met, and the finishing mill can accurately control the deformation amount of each pass to 10%.

[0052] Rolling process control: During the rough rolling process, the rolling passes and reduction amount are reasonably set according to the size and material characteristics of the ingot to ensure that the ingot can be deformed smoothly and the internal structure is uniform. The online induction heating device between rough rolling and finishing rolling raises the steel temperature to 950°C and maintains it for 2 minutes. The online induction heating device uses the principle of electromagnetic induction to generate an induced current inside the steel, thereby achieving rapid heating. It has high heating efficiency and can accurately control the heating temperature and time of the steel. During the finishing rolling process, the deformation amount of each pass is strictly controlled to ensure the dimensional accuracy and surface quality of the steel. During finishing rolling, the interval time between each pass should be reasonably controlled to avoid excessive reduction in the steel temperature and affect the rolling performance.

[0053] 4. Three-stage cooling:

[0054] Selection of cooling equipment: A specially designed three-stage cooling equipment is used to accurately control the cooling rate at different stages. The cooling rate in the first stage is 20℃ / s. The steel is quickly cooled to 600℃ through strong air cooling or water cooling (selected according to actual conditions). During the cooling process, the temperature of the steel is monitored in real time through a temperature sensor and fed back to the control system to adjust the flow and pressure of the cooling medium to ensure a stable cooling rate. The cooling rate in the second stage is 10℃ / s. A relatively mild cooling method is used to cool the steel to 400℃. This stage is mainly to control the transformation of the internal structure of the steel to avoid excessive internal stress. The cooling rate in the third stage is 5℃ / s, which allows the steel to slowly cool to room temperature to further stabilize the structure and performance of the steel.

[0055] 5. Aging treatment and shot peening:

[0056] Aging treatment: The cooled steel is placed in an aging furnace, the aging temperature is set to 550°C, and the aging time is 5 hours. The aging furnace uses a precise temperature control system to ensure the stability of the aging temperature, with the error controlled within ±5°C. During the aging treatment, the alloy elements inside the steel will precipitate, strengthen the matrix structure, and improve the strength and hardness of the steel;

[0057] Shot peening: After aging treatment, double-medium shot peening is carried out. First, pre-shot peening is carried out with glass beads with a particle size of 0.2mm and a shot peening pressure of 0.2MPa. The pre-shot peening equipment uses a shot peening machine with precisely adjustable pressure. The glass beads are accelerated and sprayed onto the steel surface by compressed air to form a compressive stress layer of a certain depth on the steel surface to improve the fatigue strength and stress corrosion resistance of the steel. During the pre-shot peening process, the shot peening angle and distance are controlled to ensure that the glass beads evenly impact the steel surface. After the pre-shot peening is completed, the main shot peening is carried out with steel shots with a particle size of 0.4mm and a shot peening pressure of 0.4MPa. The main shot peening further increases the compressive stress on the steel surface, refines the surface grains, and improves the surface hardness and wear resistance. During the main shot peening, the parameters of the shot peening machine are adjusted according to the shape and size of the steel to ensure uniform and consistent shot peening effect.

[0058] (III) Performance test:

[0059] 1. Mechanical properties test:

[0060] Tensile test: A universal material testing machine was used for the tensile test. The test was carried out in accordance with the national standard GB / T228.1-2010 "Tensile test of metallic materials - Part 1: Room temperature test method". Standard tensile specimens were prepared. The shape and size of the specimens met the standard requirements. Tensile force was slowly applied on the testing machine until the specimen broke. The yield strength, tensile strength and elongation were recorded. After testing, the yield strength was 500MPa, the tensile strength was 650MPa, and the elongation was 28%, which met the high-strength requirements.

[0061] Impact test: The impact test was carried out in accordance with GB / T229-2007 "Metallic Materials Charpy Pendulum Impact Test Method", and the impact specimens were prepared. The impact toughness of the steel was measured on an impact testing machine. The test results showed that the steel had good impact toughness and could resist impact loads to a certain extent.

[0062] 2. Corrosion resistance test:

[0063] Neutral salt spray test: refer to GB / T10125-2012 "Artificial atmosphere corrosion test salt spray test" for neutral salt spray test. Place the sample in a salt spray test chamber. The temperature in the test chamber is controlled at (35±2)℃. The salt spray solution is a 5% NaCl solution with a spray pressure of (70~170)kPa and a spray volume of (1~2)mL / (h·80cm 2), the test period is 720 hours. After the test, take out the sample, clean and dry it, weigh it, and calculate the corrosion rate. The tested corrosion rate is 0.008mm / a, which has good corrosion resistance.

[0064] 3. Antioxidant test:

[0065] High temperature oxidation test: According to GB / T24133-2009 "Metallic Materials Room Temperature Uniaxial Tensile Test Method", the high temperature oxidation test was carried out. The sample was placed in a high temperature oxidation furnace and kept at 800°C for 100 hours. During the test, the atmosphere in the furnace was air. The mass change of the sample before and after the test was measured by accurate weighing equipment, and the oxidation weight gain rate was calculated. The test results showed that the oxidation weight gain rate was 0.1mg / cm 2 ·h, showing excellent antioxidant properties.

[0066] 4. Microstructure observation:

[0067] Preparation of metallographic samples: Cut appropriate metallographic samples from the prepared weathering steel, and prepare metallographic samples with smooth surface and no scratches through steps such as inlaying, grinding and polishing;

[0068] Microstructure observation: metallographic microscope was used for observation, and the magnification ranged from 100 times to 1000 times. The morphology and characteristics of the microstructure were observed, and it was found that the microstructure was ferrite + pearlite + dispersed carbonitride particles + a small amount of nano-scale oxide particles. The ferrite grain size was 3μm. The grain size was measured and statistically analyzed by image analysis software to ensure the accuracy of the measurement results. The pearlite interlamellar spacing was 0.1μm, and the image analysis method was also used for measurement. The average size of the carbonitride particles was 10nm, and the oxide particles were mainly Cr2O3 and ZrO2, with an average size of 5nm. The distribution and structural characteristics of these nano-scale particles were further observed and analyzed by transmission electron microscopy (TEM).

[0069] Embodiment 2:

[0070] (I) Chemical composition design:

[0071] The chemical composition is calculated by weight percentage: C content is 0.08%, Si content is 0.25%, Mn content is 1.00%, P content is 0.010%, S content is 0.004%, Nb content is 0.035%, V content is 0.08%, Zr content is 0.03%, Cu content is 0.50%, Cr content is 0.80%, Ni content is 0.40%, Mo content is 0.20%, and it also contains 0.005% by weight of rare earth element RE, and lanthanum La and cerium Ce in the rare earth elements exist in a mass ratio of 2:1. The thickness of weathering steel is 25mm.

[0072] (II) Preparation method:

[0073] 1. Electroslag remelting and casting ingots:

[0074] Raw material selection and proportioning: According to the design requirements of chemical composition, carefully select the raw materials of each element. For the rare earth element RE, a rare earth alloy containing lanthanum (La) and cerium (Ce) is used to add, ensuring that the mass ratio of lanthanum and cerium is 2:1. During the batching process, the weighing accuracy of each raw material is strictly controlled, and the error is controlled within ±0.01%;

[0075] Optimization of electroslag remelting process: In the electroslag remelting process, in addition to controlling conventional refining parameters, the slag system composition and refining time are optimized for the addition of rare earth elements. The slag system used can effectively promote the uniform distribution of rare earth elements while reducing the burn-up of rare earth elements. The refining time is extended to [X] hours to ensure that the molten steel is fully refined, the content of impurity elements is further reduced, and the rare earth elements are fully alloyed with other alloying elements. When casting steel ingots, vacuum casting technology is used to reduce the gas content in the molten steel and improve the density of the steel ingot.

[0076] 2. Ingot heating:

[0077] Adjustment of heating parameters: The heating temperature of the steel ingot is 1230℃, and the heat preservation is 3 hours. The heating power is controlled in sections, and the power of the first section is 65% of the maximum power, and the power of the second section is 85% of the maximum power. According to the size and material characteristics of the steel ingot, the heating time and power curve are optimized to ensure that the internal structure of the steel ingot is evenly heated to avoid overheating or overburning;

[0078] Precise control of furnace atmosphere: The volume ratio of hydrogen content in the furnace atmosphere is 5%. Before the mixed gas is introduced, the furnace is strictly deoxidized and high-purity argon is used to purge the furnace for many times. Then argon and hydrogen are introduced according to the set gas flow and ratio. The composition of the furnace atmosphere is monitored in real time by an online gas analyzer, and the gas flow is adjusted in time to ensure that the hydrogen content is stable at about 5%. This ensures that the steel ingot is heated in a reducing atmosphere, further improving the purity and quality of the steel.

[0079] 3. Hot rolling:

[0080] Rolling process optimization: during hot rolling, the starting temperature of rough rolling is 1130℃, the final rolling temperature of rough rolling is 1030℃, the starting temperature of finishing rolling is 960℃, the final rolling temperature of finishing rolling is 850℃, and the deformation of each pass of finishing rolling is 13%. According to the chemical composition and thickness changes of steel, the rolling procedures of rough rolling and finishing rolling are optimized, and the reduction amount of each pass is reasonably allocated to ensure that the steel is uniformly deformed during the rolling process and the internal structure is well improved. The online induction heating device between rough rolling and finishing rolling raises the steel temperature to 1000℃ and maintains it for 1.5 minutes. By optimizing the parameters of the induction heating device, such as frequency, power, etc., the steel temperature can be quickly and evenly increased, and the holding time can be accurately controlled so that the steel reaches the optimal rolling temperature before entering the finishing rolling, which is beneficial to improving the performance of the steel after finishing rolling.

[0081] 4. Three-stage cooling:

[0082] The third stage cooling rate is 10℃ / s, which allows the steel to slowly cool to room temperature. During the cooling process, the cooling rate of each stage is precisely controlled according to the phase change characteristics of the steel to ensure that the internal structure of the steel is transformed into an ideal ferrite + pearlite structure. At the same time, the dispersed carbonitride particles and a small amount of nano-oxide particles can be evenly precipitated. An advanced cooling control system is used to monitor the temperature and cooling rate of the steel in real time. By adjusting the flow, temperature and injection method of the cooling medium, precise control of the cooling process is achieved. For example, in the first stage of cooling, a combination of high-pressure air cooling and water mist spray is used to quickly take away the heat from the steel surface; the second stage of cooling appropriately reduces the air cooling intensity to increase the temperature uniformity inside and on the surface of the steel; the third stage of cooling mainly relies on natural convection heat dissipation to cool the steel slowly and reduce the generation of internal stress.

[0083] 5. Aging treatment and shot peening:

[0084] Optimization of aging treatment: The aging treatment temperature is 600℃, the aging time is 4 hours, and a high-precision aging furnace is used. The temperature uniformity in the furnace is controlled within ±3℃ to ensure uniform transformation of the internal structure of the steel during the aging treatment. During the aging treatment, the hardness change of the steel is monitored in real time to verify the aging effect. The aging temperature and time are adjusted in time according to the hardness change to achieve the best strengthening effect of the steel.

[0085] Improvement of shot peening process: During shot peening, pre-peening is performed with glass beads of 0.25 mm in diameter and a peening pressure of 0.25 MPa. The pre-peening equipment uses an advanced CNC shot peening machine, which can accurately control the spray angle, speed and flow rate of the glass beads to ensure the formation of a uniform and stable compressive stress layer on the steel surface. After pre-peening, the roughness and residual stress of the steel surface are tested. The pre-peening parameters are adjusted according to the test results to achieve the ideal surface state. Then, the main shot peening is performed with steel shots of 0.5 mm in diameter and a peening pressure of 0.5 MPa. During the main shot peening process, an automated shot peening path planning system is used according to the shape and size of the steel to ensure that the steel shots can evenly impact all parts of the steel surface, further improving the surface hardness, wear resistance and fatigue strength of the steel.

[0086] (III) Performance test:

[0087] 1. Mechanical properties test:

[0088] Tensile test: A tensile test was conducted again in accordance with the national standard GB / T228.1-2010, and multiple groups of samples were prepared for repeated testing to ensure the accuracy and reliability of the test results. The test results showed that the yield strength was 550 MPa, the tensile strength was 700 MPa, and the elongation was 30%. Compared with Example 1, the yield strength increased by 10%, the tensile strength increased by 7.7%, and the elongation increased by 7.1%. This is mainly due to the optimization of the chemical composition and the improvement of the preparation process, which makes the matrix structure of the steel more compact and the strengthening effect of the alloy elements is more fully exerted;

[0089] Impact test: A series of impact tests were conducted, changing the impact test temperature from room temperature to low temperature (such as -20°C, -40°C, etc.) to study the change pattern of the impact toughness of steel at different temperatures. The test results showed that within a wide temperature range, the impact toughness of the steel remained at a high level, indicating that it has good low-temperature toughness and can adapt to the use requirements under different ambient temperatures.

[0090] 2. Corrosion resistance test:

[0091] Neutral salt spray test: The neutral salt spray test cycle was extended to 1000 hours to further evaluate the long-term corrosion resistance of the steel. After the test, a more detailed corrosion morphology analysis was performed on the sample. The microstructure and distribution characteristics of the corrosion products were observed using a scanning electron microscope (SEM). The tested corrosion rate was 0.006 mm / a, which was 25% lower than that in Example 1, indicating that the addition of rare earth elements and the optimization of the preparation process effectively improved the corrosion resistance of the steel. The analysis of the corrosion products showed that the corrosion products were denser and could effectively block further intrusion of the corrosive medium.

[0092] 3. Antioxidant test:

[0093] High temperature oxidation test: In the high temperature oxidation test, the oxidation time was increased to 200 hours, and the growth rate and structural changes of the oxide film on the steel surface were monitored during the oxidation process. The test results showed that the oxidation weight gain rate was 0.08 mg / cm 2 h, which is 20% lower than that of Example 1. This is due to the reasonable combination of alloy elements in the chemical composition, especially the effects of elements such as Cr and Zr, as well as the control of the purity and organizational uniformity of the steel in the preparation process, which enables a more stable and dense oxide film to be formed on the surface of the steel, effectively preventing the diffusion of oxygen atoms and improving the anti-oxidation performance.

[0094] 4. Microstructure observation:

[0095] Metallographic sample preparation: In the process of metallographic sample preparation, a more sophisticated polishing process is adopted, such as the use of nano-level polishing agents, to obtain a higher quality metallographic sample surface, which facilitates a clearer observation of the microstructure.

[0096] Microstructure observation: The microstructure was further observed by metallographic microscope and transmission electron microscope (TEM), and it was found that in the microstructure, the ferrite grain size was 5μm, which was larger than that in Example 1. This was due to the change in grain growth dynamics caused by changes in chemical composition and process parameters. The pearlite interlamellar spacing was 0.2μm, the average size of carbonitride particles was 30nm, and the average size of oxide particles was 10nm. Compared with Example 1, the size of carbonitride particles and oxide particles increased. This is because the increase in the alloying element content promoted the precipitation and growth of these particles. The changes in these microstructural characteristics are closely related to the changes in steel properties. For example, the moderate growth of ferrite grain size improves the toughness of steel to a certain extent, while the reasonable distribution and size changes of carbonitride and oxide particles help to improve the strength and corrosion resistance of steel.

[0097] Embodiment three:

[0098] (I) Chemical composition design:

[0099] Chemical composition by weight percentage: C content is 0.10%, Si content is 0.35%, Mn content is 1.20%, P content is 0.015%, S content is 0.005%, Nb content is 0.045%, V content is 0.10%, Zr content is 0.05%, Cu content is 0.60%, Cr content is 1.00%, Ni content is 0.50%, Mo content is 0.30%, and it contains 0.008% by weight of rare earth elements RE, and lanthanum La and cerium Ce in the rare earth elements exist in a mass ratio of 3:1. The thickness of weathering steel is 35mm.

[0100] (II) Preparation method

[0101] 1. Electroslag remelting and casting ingots:

[0102] Raw material quality control: During the raw material preparation stage, strict quality inspections are carried out on the raw materials of each element to ensure that their purity and impurity content meet the requirements. For key alloying elements such as Nb, V, Zr, etc., high-purity ferroalloys are used and pre-treated to remove surface oxides and other impurities. The addition of rare earth elements RE adopts special coating technology to wrap the rare earth elements in a layer of inert materials to prevent excessive burning and segregation of rare earth elements during the smelting process. After the ingredients are prepared, they are fully stirred and mixed to ensure that the elements are evenly distributed;

[0103] Innovation in electroslag remelting process: During the electroslag remelting process, a new type of slag system is used, which has higher desulfurization and dephosphorization capabilities and can effectively control the shape and size of inclusions. During the refining process, electromagnetic stirring technology is introduced to enable the molten steel to produce strong convection during the refining process, promote the refining reaction, and improve the uniformity and purity of the molten steel. When pouring steel ingots, continuous casting technology is used. By optimizing the continuous casting process parameters, such as pouring speed, cooling intensity, etc., steel ingots with good surface quality and dense internal structure are obtained, reducing the occurrence of casting defects.

[0104] 2. Ingot heating:

[0105] Heating parameter optimization: heat the steel ingot to 1280℃ and keep it warm for 2.5 hours. According to the thickness and material characteristics of the steel ingot, the segmented control of the heating power is further optimized. The power of the first section is 70% of the maximum power, and the duration is accurately calculated according to the initial temperature and size of the steel ingot to ensure that the steel ingot can be heated evenly. The power of the second section is 90% of the maximum power. When approaching the target heating temperature, the heating rate is appropriately reduced to prevent local overheating of the steel ingot. The volume ratio of hydrogen content in the furnace is 8%. Through the advanced gas mixing and control system, the precise control of hydrogen content is achieved. During the heating process, the pressure and composition changes of the furnace atmosphere are monitored in real time, and the gas flow rate is adjusted in time to ensure the stability and reducibility of the furnace atmosphere.

[0106] 3. Hot rolling:

[0107] Rolling process innovation: during hot rolling, the starting temperature of rough rolling is 1180℃, the final rolling temperature of rough rolling is 1080℃, the starting temperature of finishing rolling is 1000℃, the final rolling temperature of finishing rolling is 870℃, and the deformation of each finishing pass is 15%. In order to meet the rolling requirements of thicker steel, a large-tonnage rolling mill is used, and the material and surface treatment of the rolling rolls are optimized to improve the wear resistance and bite ability of the rolling rolls. An intelligent temperature control system is introduced in the online induction heating device between rough rolling and finishing rolling. According to the real-time temperature of the steel and the rolling process requirements, the power and frequency of the induction heating are automatically adjusted to ensure that the steel temperature is accurately raised to 1050℃ and maintained for 1 minute. At the same time, during the rolling process, advanced plate shape control technologies are used, such as hydraulic bending rolls and shifting rolls, to ensure the plate shape accuracy of the steel and reduce the generation of residual stress.

[0108] 4. Three-stage cooling:

[0109] Cooling strategy adjustment: three-stage cooling: the first stage cooling rate is 30℃ / s, cooling to 700℃; the second stage cooling rate is 20℃ / s, cooling to 500℃; the third stage cooling rate is 15℃ / s, cooling to room temperature. In view of the characteristics of thicker steel, differentiated cooling methods are adopted during the cooling process. The first stage cooling adopts a combination of strong wind cooling and water mist cooling, focusing on controlling the cooling rate of the steel surface to form a suitable surface structure. The second stage cooling, based on air cooling, appropriately adjusts the air cooling angle and wind speed to make the cooling rate inside and on the surface of the steel more coordinated. The third stage cooling adopts a slow cooling method, such as setting a heat insulation device in the cooling channel to slow down the cooling rate of the steel, reduce the generation of internal stress, and ensure the overall uniform performance of the steel.

[0110] 5. Aging treatment and shot peening:

[0111] Refined aging treatment: The aging treatment temperature is 650℃, the aging time is 3 hours, and an aging furnace with high-precision temperature control and atmosphere protection functions is used. During the aging process, the atmosphere in the furnace is kept inert gas protection to prevent the surface oxidation of the steel. By real-time monitoring of the hardness, strength and microstructure changes of the steel, the aging treatment process is accurately controlled to ensure the best aging effect;

[0112] Precision shot peening: Shot peening is first performed with 0.3mm glass beads for pre-peening at a pressure of 0.3MPa. The pre-peening equipment uses a high-precision pressure control system and an automated shot peening operation platform, which can automatically adjust the shot peening parameters according to the surface shape and size of the steel to ensure the uniformity and consistency of the pre-peening. After pre-peening, non-destructive testing techniques such as ultrasonic testing are used to detect the residual stress distribution on the steel surface. The pre-peening process is optimized based on the test results, and then the main shot peening is performed with 0.6mm steel shots at a pressure of 0.6MPa. During the main shot peening process, computer simulation technology is used to optimize the spray trajectory and impact energy distribution of the steel shots, so that the steel surface obtains a uniform and ideal strengthening effect, thereby improving the surface performance and overall service life of the steel.

[0113] (III) Performance test:

[0114] 1. Mechanical properties test:

[0115] Tensile test: Continue to carry out tensile test according to the standard, and analyze the fracture of tensile specimen in detail. Use scanning electron microscope (SEM) to observe the microscopic morphology of fracture and analyze the fracture mechanism. The test results show that the yield strength reaches 580MPa, the tensile strength is 720MPa, and the elongation is 32%. Compared with Example 1 and Example 2, the yield strength is increased by 16% and 5.5%, the tensile strength is increased by 10.8% and 2.9%, and the elongation is increased by 14.3% and 6.7%, respectively. This is mainly due to the further increase of alloy element content in chemical composition and the continuous optimization of preparation process, which makes the matrix strengthening effect of steel more significant. At the same time, the optimization of microstructure also helps to improve the plastic deformation capacity of steel.

[0116] Hardness test: Use Rockwell hardness tester or Vickers hardness tester to test the hardness of steel. The test parts include the surface and the core. The distribution law of hardness in different parts of steel is studied. The test results show that the surface hardness of steel is higher and the core hardness is slightly lower than the surface, but the overall hardness distribution is relatively uniform. This shows that shot peening and aging treatment processes have good strengthening effects on the surface and internal structure of steel, and the internal structure of steel is more uniform.

[0117] 2. Corrosion resistance test:

[0118] Neutral salt spray test: The neutral salt spray test cycle was further extended to 1500 hours, and samples were taken out regularly during the test for electrochemical tests, such as open circuit potential and polarization curve measurements, to analyze the corrosion behavior of the steel from an electrochemical perspective. After the test, the composition changes of the corrosion products were studied by means of energy spectrum analysis (EDS) and other means. The tested corrosion rate was 0.005 mm / a, which was further reduced by 37.5% and 16.7% compared with Examples 1 and 2, respectively. This shows that with the optimization of the chemical composition and the improvement of the preparation process, a more stable and dense corrosion protection layer is formed on the surface of the steel, which effectively inhibits the corrosion reaction.

[0119] 3. Antioxidant test:

[0120] High temperature oxidation test: In the high temperature oxidation test, the oxidation time was extended to 300 hours, and in-situ observation techniques, such as high temperature microscopy, were used during the oxidation process to observe the growth and evolution of the oxide film on the steel surface in real time. The test results showed that the oxidation weight gain rate was 0.06 mg / cm 2 ·h, compared with Example 1 and Example 2, the oxidation weight gain rate is reduced by 40% and 25% respectively. This is because the synergistic effect of the alloy elements and the fine regulation of the steel microstructure by the preparation process enable the steel to form a continuous and dense oxide film at high temperature, which effectively prevents the diffusion of oxygen and improves the oxidation resistance.

[0121] 4. Microstructure observation:

[0122] Metallographic sample preparation: In the process of metallographic sample preparation, the focused ion beam (FIB) technology is used to prepare the sample in micro-area in order to observe the local detailed characteristics of the microstructure, such as the distribution of precipitates at the grain boundary;

[0123] Microstructure observation: The microstructure was observed in depth through a metallographic microscope and a transmission electron microscope (TEM). It was found that in the microstructure, the ferrite grain size was 8 μm, the pearlite interlamellar spacing was 0.3 μm, the average carbonitride particle size was 50 nm, and the average oxide particle size was 20 nm. Compared with Example 1 and Example 2, the ferrite grain size has grown. This is due to the grain growth caused by the higher heating temperature and the longer holding time. However, due to the increase of alloying elements and the optimization of the microstructure, such as the reasonable distribution and size change of carbonitride and oxide particles, the performance of the steel is not reduced due to grain growth. On the contrary, it shows better comprehensive performance in terms of strength, toughness and corrosion resistance.

[0124] 4. Comparative analysis of embodiments:

[0125] 1. Comparison of chemical composition:

[0126] In Examples 1 to 3, the contents of basic elements such as C, Si, and Mn vary. As the examples progress, the C content increases from 0.06% to 0.10%, the Si content increases from 0.15% to 0.35%, and the Mn content increases from 0.80% to 1.20%. The increase of these elements helps to improve the strength of the steel, but corresponding adjustments are also required in other processes to avoid adverse effects on toughness and welding performance. At the same time, the contents of alloying elements Nb, V, Zr, Cu, Cr, Ni, Mo and rare earth elements RE also gradually change, and their reasonable combination plays a key role in improving the performance of steel. For example, the addition of rare earth element RE, in Examples 2 and 3, its content is 0.005% and 0.008% respectively, and the mass ratios of lanthanum La and cerium Ce are different, which affects the morphology and distribution of inclusions in the steel, thereby improving the comprehensive performance of the steel.

[0127] 2. Preparation process comparison:

[0128] Electroslag remelting and casting ingots:

[0129] The first embodiment adopts conventional electroslag remelting and casting processes, the second embodiment optimizes the slag system composition and refining time during the electroslag remelting process, and adopts vacuum casting technology, and the third embodiment is further innovative, adopting a new slag system, electromagnetic stirring technology and continuous casting technology. These process improvements make the refining effect of molten steel better and better, the quality of ingots is continuously improved, and internal defects are gradually reduced, laying a foundation for subsequent processing and performance improvement;

[0130] Ingot heating:

[0131] The heating temperature is 1180°C in Example 1, 1230°C in Example 2, and 1280°C in Example 3. The holding time and the step-by-step variable power control are also different. As the heating temperature increases, the uniformity of the internal structure of the steel ingot and the degree of solid solution of the alloy elements change. A higher heating temperature helps to fully dissolve the alloy elements, but precise control is also required to prevent overheating. The hydrogen content in the furnace atmosphere increases from 3% (Example 1) to 8% (Example 3). A stronger reducing atmosphere is beneficial to further remove impurities on the surface of the steel ingot and improve the purity of the steel.

[0132] Hot Rolled:

[0133] The rolling temperature and deformation parameters of each embodiment are different. The rough rolling and finishing rolling temperatures of embodiment three are relatively high, and the maximum deformation of each finishing rolling pass is 15%. Higher rolling temperature and appropriate deformation are helpful to improve the microstructure of steel, refine grains, and improve the performance of steel. At the same time, the role of the online induction heating device in each embodiment is also reflected. The intelligent temperature control system of embodiment three can control the temperature of steel more accurately to ensure the smooth progress of the rolling process and performance optimization.

[0134] Three-stage cooling:

[0135] The cooling rate is gradually adjusted in each embodiment. The fastest cooling rate in the first stage of Embodiment 3 is 30°C / s, the second stage is 20°C / s, and the third stage is 15°C / s. Different cooling rate strategies adapt to steels with different chemical compositions and thicknesses. The transformation of the internal structure of the steel, such as the ratio of ferrite and pearlite, the precipitation of carbonitride and oxide particles, etc., is regulated by controlling the cooling rate, thereby affecting the strength, toughness, corrosion resistance and other properties of the steel.

[0136] Aging treatment and shot peening:

[0137] The aging treatment temperature and time vary in each embodiment. The aging temperature of Embodiment 3 is as high as 650°C, and the shortest aging time is 3 hours. In terms of shot peening, the particle sizes of glass beads and steel shots and the shot peening pressure are also different. The adjustment of these process parameters is to adapt to steels with different chemical compositions and microstructural states. The alloy elements are precipitated and the matrix is ​​strengthened through aging treatment. Shot peening introduces favorable residual stress on the surface of the steel, refines the surface grains, improves the surface properties, and thus improves the overall performance of the steel.

[0138] 3. Performance comparison:

[0139] Mechanical properties:

[0140] The yield strength is 500 MPa in Example 1, 550 MPa in Example 2, and 580 MPa in Example 3; the tensile strength is increased from 650 MPa in Example 1 to 720 MPa in Example 3; and the elongation is increased from 28% in Example 1 to 32% in Example 3. It can be seen that with the optimization of chemical composition and the improvement of preparation process, the strength and plasticity of steel are improved. This is because the reasonable combination of alloy elements enhances the matrix strength, and the optimization of microstructure such as grain refinement, reasonable distribution of carbonitride and oxide particles, etc. improves the deformation ability and bearing capacity of steel.

[0141] Corrosion resistance:

[0142] The corrosion rate in the neutral salt spray test is 0.008 mm / a in Example 1, 0.006 mm / a in Example 2, and 0.005 mm / a in Example 3. The corrosion rate gradually decreases, indicating that the corrosion resistance of the steel is continuously improved. This is mainly due to the effect of corrosion-resistant elements such as Cr and Cu in the chemical composition and the formation of a dense corrosion protection layer in the microstructure. The addition of rare earth elements also improves the morphology and distribution of inclusions, reduces corrosion sources, and thus improves corrosion resistance.

[0143] Antioxidant properties:

[0144] The oxidation weight gain rate of the 800°C high temperature oxidation test in Example 1 is 0.1 mg / cm 2 h, Example 2: 0.08 mg / cm 2 h, Example 3: 0.06 mg / cm 2 ·h. The decrease in oxidation weight gain rate shows that the oxidation resistance of steel is getting better and better. This is because alloy elements such as Cr and Zr form a stable oxide film, and the optimization of the microstructure in the preparation process makes the oxide film more continuous and dense, which effectively prevents the diffusion of oxygen atoms and improves the oxidation resistance.

[0145] Microstructure:

[0146] The ferrite grain size increases from 3 μm in Example 1 to 8 μm in Example 3, the pearlite lamellar spacing increases from 0.1 μm to 0.3 μm, the average size of carbonitride particles increases from 10 nm to 50 nm, and the average size of oxide particles increases from 5 nm to 20 nm. Although the grain size and particle size have changed, due to the increase of alloying elements and the optimization of the process, the microstructure as a whole is more conducive to the improvement of steel performance. For example, the appropriate distribution of carbonitride and oxide particles plays a role of dispersion strengthening, which to a certain extent compensates for the adverse effects that may be caused by grain growth, and cooperates with other properties such as corrosion resistance and oxidation resistance to jointly improve the comprehensive performance of the steel.

[0147] Through the detailed description and comparative analysis of the above embodiments, it can be seen that the high-strength, oxidation-resistant and weather-resistant steel and its preparation method of the present invention have significant advantages in chemical composition design, preparation process control and performance improvement. Its intelligent production system can effectively ensure the stability and consistency of product quality, meet various performance requirements such as high strength, oxidation resistance and weather resistance, and have broad application prospects in the fields of construction, bridges, machinery manufacturing, etc. It can provide high-performance material support for related industries and promote technological progress and development in the industry.

[0148] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength oxidation-resistant weathering steel, characterized in that: The weathering steel has a C content of 0.06%-0.10%, a Si content of 0.15%-0.35%, a Mn content of 0.80%-1.20%, a P content of no more than 0.015%, a S content of no more than 0.005%, a Nb content of 0.025%-0.045%, a V content of 0.05%-0.10%, a Zr content of 0.02%-0.05%, a Cu content of 0.40%-0.60%, a Cr content of 0.60%-1.00%, a Ni content of 0.30%-0.50%, a Mo content of 0.10%-0.30%, and the rest is Fe and unavoidable impurities; The thickness of the weathering steel is between 20mm and 35mm.

2. The high-strength oxidation-resistant weathering steel according to claim 1, characterized in that: The weathering steel contains 0.003%-0.008% by weight of rare earth element RE, and lanthanum La and cerium Ce in the rare earth elements are present in a mass ratio of 2:1-3:

1.

3. The high-strength oxidation-resistant weathering steel according to claim 1, characterized in that: The yield strength of the weathering steel is not less than 500MPa, the tensile strength is not less than 650MPa, the elongation is not less than 28%, the corrosion rate in the neutral salt spray test is not more than 0.008mm / a, and the oxidation weight gain rate in the 800℃ high temperature oxidation test is not more than 0.1mg / cm 2 ·h.

4. The high-strength oxidation-resistant weathering steel according to claim 1, characterized in that: The microstructure of the weathering steel is ferrite + pearlite + dispersed carbonitride particles + a small amount of nanometer-sized oxide particles, wherein the ferrite grain size is 3μm-8μm, the pearlite interlamellar spacing is 0.1μm-0.3μm, the average size of the carbonitride particles is 10nm-50nm, and the oxide particles are mainly Cr2O3 and ZrO2, with an average size of 5nm-20nm.

5. A method for rolling high-strength anti-oxidation weathering steel, which is applicable to the high-strength anti-oxidation weathering steel according to claims 1 to 4, characterized in that: The specific steps of the rolling method are: a. The chemical composition of claim 1 is prepared by electroslag remelting to smelt molten steel, and then cast into ingots after refining; b. Heating the steel ingot, heating temperature 1180℃-1280℃, keeping warm for 2.5-3.5 hours, using segmented variable power during heating, the first stage power is 60%-70% of the maximum power, the second stage power is 80%-90% of the maximum power; c. After hot rolling, the steel ingot is heated, the starting temperature of rough rolling is 1080℃-1180℃, the final rolling temperature of rough rolling is 980℃-1080℃, the starting temperature of finishing rolling is 920℃-1000℃, the final rolling temperature of finishing rolling is 830℃-870℃, and the deformation amount of each pass during finishing rolling is 10%-15%; d. The hot-rolled steel is cooled in three stages. The first stage is cooled at a rate of 20°C / s-30°C / s to 600°C-700°C. The second stage is cooled at a rate of 10°C / s-20°C / s to 400°C-500°C. The third stage is cooled at a rate of 5°C / s-15°C / s to room temperature. e. After cooling, the steel is subjected to aging treatment at a temperature of 550°C-650°C for 3-5 hours. After aging treatment, shot peening is performed with a shot peening intensity of 0.3mm-0.5mm.

6. The high-strength oxidation-resistant weathering steel according to claim 5, characterized in that: In the step b, when the steel ingot is heated, the atmosphere in the furnace is a mixed atmosphere of argon and hydrogen, and the volume ratio of hydrogen content is 3%-8%.

7. The high-strength anti-oxidation weathering steel rolling method according to claim 5, characterized in that: In the step c, an online induction heating device is arranged between the rough rolling and the finish rolling to raise the temperature of the steel to 950° C.-1050° C. and maintain it for 1-2 minutes.

8. The high-strength anti-oxidation weathering steel rolling method according to claim 5, characterized in that: In the step e, the shot peening strengthening after aging treatment adopts dual-medium shot peening, specifically: glass beads are used for pre-shot peening, the glass beads have a particle size of 0.2mm-0.3mm, and the shot peening pressure is 0.2MPa-0.3MPa. After the pre-shot peening, steel shots are used for main shot peening, the steel shots have a particle size of 0.4mm-0.6mm, and the shot peening pressure is 0.4MPa-0.6MPa.

9. The high-strength anti-oxidation weathering steel rolling method according to claim 5, characterized in that: The rolling method comprises an intelligent production system, wherein the system comprises a raw material batching unit, an electroslag remelting unit, an ingot heating unit, a hot rolling unit, a three-stage cooling unit, an aging treatment unit, a dual-medium shot peening unit and a central control unit; The raw material batching unit performs accurate batching according to the chemical composition described in claim 1; The electroslag remelting unit performs the electroslag remelting process to refine the molten steel and cast the steel ingots; The ingot heating unit has the functions of accurately controlling the heating temperature at 1180℃-1280℃, holding time of 2.5-3.5 hours, segmented variable power: the first stage power is 60%-70% of the maximum power, the second stage power is 80%-90% of the maximum power, and the furnace atmosphere, in which argon and hydrogen are mixed, with a hydrogen content of 3%-8% by volume, and transmitting data to the central control unit; The hot rolling unit can be operated at a starting temperature of 1080°C-1180°C for rough rolling and a final rolling temperature of 980°C for rough rolling. -1080℃, finishing rolling start temperature 920℃-1000℃, finishing rolling final rolling temperature 830℃-870℃ and finishing rolling deformation of 10%-15% for each pass, and the steel temperature is raised to 950℃-1050℃ and maintained for 1-2 minutes by an online induction heating device between rough rolling and finishing rolling, while the rolling force and rolling temperature are monitored in real time and fed back to the central control unit; The three-stage cooling unit cools the steel to 600-700°C at a first stage cooling rate of 20°C / s-30°C / s, to 400-500°C at a second stage cooling rate of 10°C / s-20°C / s, and to room temperature at a third stage cooling rate of 5°C / s-15°C / s according to the instructions of the central control unit; The aging treatment unit accurately controls the aging temperature at 550℃-650℃ and the aging time at 3-5 hours. The dual-media shot peening unit can perform pre-shot peening with glass beads of 0.2mm-0.3mm in diameter and shot peening pressure of 0.2MPa-0.3MPa as required, and then perform main shot peening with steel shots of 0.4mm-0.6mm in diameter and shot peening pressure of 0.4MPa-0.6MPa. The central control unit conducts real-time monitoring, data collection and analysis of the entire production process, coordinates the work of each unit based on the feedback data from each unit, and realizes intelligent production control.

Citation Information

Patent Citations

  • Heat resistant steel, and heat resistant steel pipe and manufacturing method thereof

    CN102330035A

  • Thick-specification weathering-resistant steel containing niobium and vanadium and rolling method thereof

    CN106435366A

  • High toughness and low yield ratio refractory and weather resistant steel with tensile strength of greater than or equal to 600MPa and production method thereof

    CN106854732A

  • Low-carbon bainite weathering resistant steel and production method thereof

    CN108570601A

  • High-yield-strength 600MPa-level hot-rolled high-strength weather-proof steel plate and production method thereof

    CN113234994A